Influence of Grinding Parameters on Surface Finish of Inconel 718 / Nurul Afizan Yaakob...[et al.] - Yaakob, Nurul Afizan; Ganesan, Hema Nanthini; Harun, Nurul Hatiqah; Raja Abdullah, Raja Izamshah; Kasim, Mohd Shahir (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
High-strength Inconel 718 is used for manufacturing critical parts of a turbine blade owing to its good mechanical properties. However, there is a drawback in the material removal process. In this paper, the grinding performance of surface finish was investigated under several cutting conditions. The variable parameters studied were traverse speed, depth of the cut and the number of passes. Historical data of the response surface methodology (RSM) was used to analyses the correlation between the variable input and output. In ANOVA, the traverse speed and depth of cut were found to be significant factors instead of the number of passes, in which the P-value is less than 0.05. The appropriate parameter settings for grinding of the Inconel 718 are 9,137 mm/min of traverse speed, 7 μm in depth of cut, and 10 passes.